Experiment study of water based photovoltaic-thermal (PV/T) collector - Nur Farhana Mohd Razali; Ahmad Fudholi; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Solar radiation can be converted to the electrical energy and thermal energy by photovoltaic panel and solar collector. In this experiment, PV/T collector was designed, fabricated and tested its performance. The experiment conducted on PV/T collector with water flow at mass flow rate 0.012 kg/s to 0.0255 kg/s. The water flow with the stainless stell absorber help the PV/T collector in increasing the convection of thermal heat transfer. The power output increase with increase of radiation. The efficiency of PVT varies with different intensity of radiation which stated in this experiment for 750 W/m2 and 900 W/m2. The analysis of energy and exergy are excuted and results show energy output for water based PV/T collector are 346 W for solar radiation 700 W/m2 and 457 W for solar radiation 900 W/m2.  Meanwhile the total exergy output compared to the PV panel without stainless stell absorber, which the exergy increased by 22.48% for 700 W/m2 and 20.87% for 900 W/m2.